Clinical and molecular characterization of mitochondrial DNA disorders in a group of Argentinian pediatric patients - Loos, Mariana Amina (2021)
Objective: To describe the clinical and molecular features of a group of Argentinian pediatric patients with mitochondrial DNA (mtDNA) disorders, and to evaluate the results of the implementation of a classical approach for the molecular diagnosis of mitochondrial diseases. Methods: Clinical data from 27 patients with confirmed mtDNA pathogenic variants were obtained from a database of 89 patients with suspected mitochondrial disease, registered from 2014 to 2020. Clinical data, biochemical analysis, neuroimaging findings, muscle biopsy and molecular studies were analyzed. Results: Patients were 18 females and 9 males, with ages at onset ranging from 1 week to 14 years (median = 4 years). The clinical phenotypes were: mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome (n = 11), Leigh syndrome (n = 5), Kearns-Sayre syndrome (n = 3), Chronic Progressive External Ophthalmoplegia (n = 2), Leber hereditary optic neuropathy (n = 2), myoclonic epilepsy associated with ragged-red fibers (n = 1) and reversible infantile myopathy with cytochrome-C oxidase deficiency (n = 3). Most of the patients harbored pathogenic single nucleotide variants, mainly involving mt-tRNA genes, such as MT-TL1, MT-TE and MT-TK. Other point variants were found in complex I subunits, like MT-ND6, MT-ND4, MT-ND5; or in MT-ATP6. The m.13513G > A variant in MT-ND5 and the m.9185 T > C variant in MT-ATP6 were apparently de novo. The rest of the patients presented large scale-rearrangements, either the ?common? deletion or a larger deletion. Conclusions: This study highlights the clinical and genetic heterogeneity of pediatric mtDNA disorders. All the cases presented with classical phenotypes, being MELAS the most frequent. Applying classical molecular methods, it was possible to achieve a genetic diagnosis in 30% of the cases, suggesting that this is an effective first approach, especially for those centers from low-middle income countries, leaving NGS studies for those patients with inconclusive results.